Structural and semantic features of light industry terms in English: a linguistic analysis - Sratdinova , Gulbakhar (The Lingua Spectrum, 2025)
This article analyzes the morphological, syntactic, and semantic features of light industry terminology in English. It identifies compounding, affixation, and blending as key word-formation processes and highlights the role of noun phrases, adjective-noun combinations, and prepositional phrases in ensuring terminological precision. Additionally, semantic relationships such as hyponymy, synonymy, polysemy, and antonymy aid in material classification and product differentiation. The findings are valuable for linguists, translators, and industry professionals, improving technical communication, translation accuracy, and terminology management. Understanding these linguistic structures enhances clarity in global trade and industrial documentation. Future research should explore AI-driven terminology tools and cross-linguistic variations to support industry advancements.